Global burden of ischemic stroke in adults aged 60 years and older from 1990 to 2021: Population-based study - Xiuen Chen; Lizhi Lu; Chao Xiao; Yining Lan; Songxin Zhong; Chao Qin; Yanyan Tang (PLoS ONE, 2025)
Background Ischemic stroke is an important public health problem. However, comprehensive data on its burden in aging populations is limited. The aim of this study is to provide an up-to-date assessment of the prevalence, incidence, mortality, disability-adjusted life years, and risk factors for ischemic stroke globally in adults aged 60 years and older from 1990 to 2021 based on population changes. Methods The Global Burden of Diseases, Injuries, and Risk Factors Study 2021 served as the data source for this study. Average annual percentage changes were estimated over the study period to quantify temporal patterns and assess trends in age-standardized rates of the prevalence, incidence, mortality, and disability-adjusted life-years of ischemic stroke. Results The significant increase in the prevalence and incidence of ischemic stroke is mainly related to population ageing and the significant increase in the number of people over 60 years of age, with the significant increase in the population over 60 years of age being the main driving force, while epidemiological changes have had the opposite effect. Critically, using the entire age population for calculations will prompt us to underestimate the burden of ischemic stroke. The burden of ischemic stroke disease is highest in older men than in older women, and the age-standardized prevalence rates, incidence rates, mortality rates, and disability-adjusted life-years rates are 26–35% higher in men than in women. High-middle sociodemographic index and Sub-Saharan Africa regions suffer the heaviest burden. Ischemic stroke health inequities widen, with less developed regions bearing a heavier ischemic stroke burden and the disparity in that burden becoming more pronounced over time. Conclusion Population aging is the primary driver of the growing burden of ischemic stroke. Our findings indicate that prevention and control of this disease remain critical public health challenges. Targeted interventions addressing modifiable risk factors could significantly reduce the global burden of ischemic stroke.